An Application of Buddhadhamma in Promoting Effective Communications in Work of Employees, Kasikornbank Public Company Limited - Thingwanichniyom, Korkiat; Changcharoen, Dr. Chompoonuch; Guttaviro, Asst. Prof. Dr., PhramahaViroj (Journal of Dhamma for Life, 2024)
The objectives of this thesis are as follows: 1) to study the application of Buddhadharma principles to promote effective communication at work of KBank employees, 2) to study the comparison of the application of Buddhadharma principles to promote effective communication at work of KBank employees with different genders, age, years of work, education level and organizational position, and 3) to study suggestions on the application of Buddhadharma principles for promoting effective work communication of KBank employees. Sample: 152 people The tool used is a questionnaire. Statistics used to analyze the data, such as frequency, percentage, mean standard deviation. T-value test and mean difference test in pairs by Scheffe method (Post Hoc). The results of the research were as follows: Analysis of the level of application of Buddhadharma principles for promoting effective communication among KBank employees Overall very high level ( = 4.33) Comparison of the level of application of Buddhadharma principles to promote effective communication among KBank employees It was found that KBank employees had different organizational age positions. The principles of Buddhist Dharma are applied to promote effective communication in the workplace. Overall, there was a statistically significant difference of .001. There was no statistically significant difference at the .05 level. 3. Suggestions on ways to promote the application of Buddhadharma principles to promote effective communication among KBank employees It was found that the problem, principles, requirements should be studied. The communication procedures within the organization should be clearer. Promote training to increase knowledge in analytical consideration. Distinguish communication within the organization more logically. Encourage activities that support personal development to increase knowledge and communication within the organization. Keywords: Buddhist principles, communication at work, application